Pengaruh Inovasi Produk Terhadap Kinerja Pemasaran PT. TPC Serta Implementasinya pada Inovasi Produk Pelampung (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This research is motivated by the problem of marketing performance at PT. TPC is seen from the innovation of the K3 Atunas buoy product. Then implement product innovation and online sales to improve PT's marketing performance. TPC. The aim of this research is to find out how strong the influence of product innovation is on marketing performance. The marketing performance variable (Y) consists of three indicators, namely sales growth (Y1), profit growth (Y2), and customer growth (Y3). Meanwhile, the product innovation variable (X) consists of three indicators, namely line expansion (X1), new products (X2), and competing products (X3). From the resulting data it can be concluded that the product innovation variable (X) influences marketing performance (Y) in a significantly positive way. Where the dominant indicator is the line expansion indicator (X1) which is strongly correlated with the sales indicator (Y1) of rX1.1Y1 = 0.481. Product innovation influences marketing performance with a value of r2 = 0.287 or 28.7%. Meanwhile, the remaining 71.3% was influenced by other variables not examined in this research.